The PDE4 Inhibitor Tanimilast Blunts Proinflammatory Dendritic Cell Activation by SARS-CoV-2 ssRNAs - Nguyen, Hoang Oanh; Schioppa, Tiziana; Tiberio, Laura; Facchinetti, Fabrizio; Villetti, Gino; Civelli, Maurizio; Del Prete, Annalisa; Sozio, Francesca; Gaudenzi, Carolina; Passari, Mauro; Barbazza, Ilaria; Sozzani, Silvano; et al. (Frontiers in Immunology, 2022)
Phosphodiesterase 4 (PDE4) inhibitors are immunomodulatory drugs approved to treat diseases associated with chronic inflammatory conditions, such as COPD, psoriasis and atopic dermatitis. Tanimilast (international non-proprietary name of CHF6001) is a novel, potent and selective inhaled PDE4 inhibitor in advanced clinical development for the treatment of COPD. To begin testing its potential in limiting hyperinflammation and immune dysregulation associated to SARS-CoV-2 infection, we took advantage of an in vitro model of dendritic cell (DC) activation by SARS-CoV-2 genomic ssRNA (SCV2-RNA). In this context, Tanimilast decreased the release of pro-inflammatory cytokines (TNF-α and IL-6), chemokines (CCL3, CXCL9, and CXCL10) and of Th1-polarizing cytokines (IL-12, type I IFNs). In contrast to β-methasone, a reference steroid anti-inflammatory drug, Tanimilast did not impair the acquisition of the maturation markers CD83, CD86 and MHC-II, nor that of the lymph node homing receptor CCR7. Consistent with this, Tanimilast did not reduce the capability of SCV2-RNA-stimulated DCs to activate CD4+ T cells but skewed their polarization towards a Th2 phenotype. Both Tanimilast and β-methasone blocked the increase of MHC-I molecules in SCV2-RNA-activated DCs and restrained the proliferation and activation of cytotoxic CD8+ T cells. Our results indicate that Tanimilast can modulate the SCV2-RNA-induced pro-inflammatory and Th1-polarizing potential of DCs, crucial regulators of both the inflammatory and immune response. Given also the remarkable safety demonstrated by Tanimilast, up to now, in clinical studies, we propose this inhaled PDE4 inhibitor as a promising immunomodulatory drug in the scenario of COVID-19.